AN EXPLORATION OF THE CONCEPT OF FALAH WELFARE IN THE MUSLIM COMMUNITY IN LANGKAT DISTRICT - Harahap, Muhammad Arfan (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
Measurement of welfare using the concept of falah needs to be implemented in an applicative manner. This study aims to analyze the factors that influence the welfare of the concept of falah and to measure the level of welfare of the people of Langkat Regency using the falah welfare index. This research method uses mixed methods with the exploratory sequential design to analyze the level of community welfare using the concept of falah welfare, which uses qualitative methods, and to measure the influence between variables, which uses quantitative methods. The research data was analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) approach. The results showed that the level of community welfare in Langkat Regency, measured using the concept of falah welfare, was still low. In addition, this study shows that simultaneously, the variables of Religiosity, Islamic Work Ethics, Islamic Consumption Ethics, and Islamic Treasure Management affect the Falah Welfare variable by 81%. The results of this study recommend that the government of Langkat Regency measure the welfare of the community using the falah welfare index to obtain different information related to the welfare conditions of the community, especially Muslims.